Prologue to the Red River Resistance: Pre-liminal Politics and the Triumph of Riel - Ens, Gerhard (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractThis paper examines the early period of the Red River Resistance before Riel and his men erected a barrier at Rivière Sale to prevent the appointed Lieutenant Governor from entering the Colony. During this early phase of the conflict, two Métis leaders, William Dease and Louis Riel, were in competition to assume the leadership of the Métis cause. This power struggle involved two different paradigms of Métis rights as the basis on which to negotiate with the Canadian government. Dease, stressing Métis aboriginal rights, was eventually defeated by Riel who emphasized French and Catholic rights. The triumph of Riel, aided by the Catholic clergy in Red River, set the tone for the larger resistance to come, and significantly impeded Riel's attempt to build a consensus in the Colony.